2017
DOI: 10.1016/j.cub.2017.10.063
|View full text |Cite
|
Sign up to set email alerts
|

Nociceptive Cortical Activity Is Dissociated from Nociceptive Behavior in Newborn Human Infants under Stress

Abstract: SummaryNewborn infants display strong nociceptive behavior in response to tissue damaging stimuli, and this is accompanied by nociceptive activity generated in subcortical and cortical areas of the brain [1, 2]. In the absence of verbal report, these nociceptive responses are used as measures of pain sensation in newborn humans, as they are in animals [3, 4]. However, many infants are raised in a physiologically stressful environment, and little is known about the effect of background levels of stress upon the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 52 publications
4
70
0
Order By: Relevance
“…Responses to noxious stimulation can be quantified through a variety of behavioral (e.g., reflex withdrawal) and physiological (e.g., rise in heart rate, fall in oxygen saturation) changes (Moultrie et al, 2017). While such surrogate measures can guide treatment options, several studies indicate that these underestimate likely pain experience in infants and possibly contribute to an under-recognition and under-treatment of infant pain (Jones et al, 2017;Slater et al, 2008). Similarly, using an isolated forearm test during anesthesia has led to the recognition that a minority of anesthetized patients are ''aware'' and responsive (Pandit et al, 2014)-alerting us to the need for better measures to assess whether these patients are also in pain (Ní Mhuircheartaigh et al, 2013).…”
Section: The Challenge Of Measuring Painmentioning
confidence: 99%
See 1 more Smart Citation
“…Responses to noxious stimulation can be quantified through a variety of behavioral (e.g., reflex withdrawal) and physiological (e.g., rise in heart rate, fall in oxygen saturation) changes (Moultrie et al, 2017). While such surrogate measures can guide treatment options, several studies indicate that these underestimate likely pain experience in infants and possibly contribute to an under-recognition and under-treatment of infant pain (Jones et al, 2017;Slater et al, 2008). Similarly, using an isolated forearm test during anesthesia has led to the recognition that a minority of anesthetized patients are ''aware'' and responsive (Pandit et al, 2014)-alerting us to the need for better measures to assess whether these patients are also in pain (Ní Mhuircheartaigh et al, 2013).…”
Section: The Challenge Of Measuring Painmentioning
confidence: 99%
“…Other neuroimaging areas being developed with potential as biomarkers, include functional neuroimaging of the spinal cord (Eippert et al, 2017;Sprenger et al, 2012;Stroman et al, 2014) and infant pain biomarkers of pain and analgesic efficacy (Moultrie et al, 2017;Slater et al, 2010). These latter studies demonstrate that pain-related behavioral measures may underestimate pain experience in infants (Jones et al, 2017).…”
Section: Neuroimaging Tools In Pain Researchmentioning
confidence: 99%
“…Recently, Jones et al reported impaired behavioural responses to painful challenges in infants experiencing high background levels of stress. Surprisingly, the cortical response was preserved (25). These results highlighted that behavioural assessment could lead to underestimation of newborn pain in the NICU.…”
Section: Discussionmentioning
confidence: 78%
“…Previous studies in infants have demonstrated the sensitivity of infant noxious-evoked cerebral activity to sleep state 15 and physiological stress 16 . To disambiguate temporally stable trait effects, arguably of higher relevance for clinical pre-emptive decision making, from temporally transient state effects, we assessed the correlation between infants' nociceptive haemodynamic response amplitude and underlying white matter microstructure using diffusion MRI (dMRI) data.…”
Section: Introductionmentioning
confidence: 99%